Car Ownership and Mode of Transport to Work in Ireland - Nicola Commins; Anne Nolan (The Economic and Social Research Institute (ESRI), 2009)
Rapid economic and demographic change in Ireland over the last decade, with associated increases in car dependence and congestion, has focused policy on encouraging more sustainable forms of travel. In this context, knowledge of current travel patterns and their determinants is crucial. In this paper, we extend earlier Irish research to examine the joint decision of car ownership and mode of transport to work. We employ cross-section micro-data from the 2006 Census of Population to estimate discrete choice models of car ownership and commuting mode choice for four subsamples of the Irish population, based on residential location. Empirical results suggest that travel and supply-side characteristics such as travel time, costs, work location and public transport availability, as well as demographic and socio-economic characteristics such as age and household composition have significant effects on these decisions.
Keywords: R41; C51; D12; 330; mode choice; car ownership; conditional logit; Ireland; Arbeitsplatz; Verkehrsmittel; Öffentlicher Personennahverkehr; Kraftfahrzeug; Irland